Концепція рабовласницької формації: виникнення, криза та сучасний стан - Павленко, Ю.В. (Археологія, 1990)
Концепция рабовладения как особой социально-экономической формации в середине 30-х годов прочно утвердилась в советской историографии. В ее подтверждение было приведено крайне недостаточно фактических данных, однако преобладавшее в то время теоретическое понимание процесса перехода от первобытности к эксплуататорскому обществу делало ее достаточно убедительной в глазах марксистской общественности. С начала 60-х годов эта концепция неоднократно подвергалась аргументированной критике. Было убедительно показано, что рабский труд в огромном большинстве регионов никогда не играл сколько-нибудь существенной роли, а его относительно широкое распространение в античном Средиземноморье объясняется рядом вполне определенных факторов. В 80-е годы была разработана и альтернативная модель становления классовых отношений, рассматривавшая данный процесс под углом товарных отношений, удельный вес рабовладельческого уклада может приобрести гипертрофированный вид. A concept of slave-owning as a peculiar socio-economica 1 structure became firmly established in Soviet historiography in the midthirties. The number of facts to substantiate this conception was quite insufficient, yet the theoretical comprehension of transition from primitivism to the exploiter society, which dominated at that time made the concept rather convincing in the opinion of Marxists. Beginning from the 60ies this concept was repeatedly subjected to well-reasoned criticism. It has been vividly shown that the slave labour never played an essential role in most regions and its relatively wide utilization in the ancient Mediterranean region is accounted for by a number of quite difinite factors. An alternative model for formation of class relations was developed in the 80ies. It considered the mentioned process as the ruling clique monopolization of the power- property right to resources and collective surplus product. In this connection it was established that the slave labour in the production sphere acquires a certain value only in transition from the early-class relations to the estate-class relations. As a rule, it is not wide-spread, yet in certain cases, as it had been in some antique centres with a high level in the development of commodity relations, the role of the slave-owning structure may be hypertrophied.